A Novel Approach to Communicate Secret Message between Users Using Sponge Function Technique on NTRU - S. Varaprasad; K.Venkata Rao; P.S. Avadhani (International Journal of Science and Engineering, 2013)
This paper presents a novel approach for a (key distribution) for secret message communication among a group (G). In order to increase security to distribute secret message (key), we introduce sponge functions using these at a specific permutation. We generate a key and distribute this key using (PKCS)(public key crypto systems), the absorbing, squeezing functions are used. In this paper an introduction part which briefs regarding sponge functions, key distribution centre, group communication and NTRU, key generation authentication, in literature review we describe about the research states of sponge functions, lightweight hash functions-KDC – NTRU. In proposed work we propose how the group communication establishes registration of users, entry and exit of a user. The encryption and decryption algorithm are used between sender and receiver. The entire proposed work is verified in VHDL and ‘MATLABS’. doi: http://dx.doi.org/10.12777/ijse.4.2.2013.44-51 [How to cite this article: Varaprasad, S., Rao, K. V., & Avadhani, P. S. (2013). A Novel Approach to Communicate Secret Message between Users Using Sponge Function Technique on NTRU. INTERNATIONAL JOURNAL OF SCIENCE AND ENGINEERING, 4(2), 44-51; doi: http://dx.doi.org/10.12777/ijse.4.2.2013.44-51]